Opposition ved Svend Bjergs disputats - Lindhardt, Jan (Religionsvidenskabeligt Tidsskrift, 1982)
The book’s line of reasoning is here identified as being that a story, from the longest novel down to the shortest narrative unit, understood as metaphor is the basis of realization. Nothing more of less than a story. Belief, conviction and understanding are expressed in a story in an irresistibly creative manner. This is pointed out as being the book’s decisively new and fertile contribution to theology. But with this in mind, the discussion concerning criteria external to the story (p. 120) or that traditions or stories can be foreign to us (pp. 268ff.) appears to be inconsistent.